The Design Of The Picture Story Book “AKU ANAK MANDIRI” As A Motivational Media For Special Need Children At Sumber Dharma Elementary School, Malang City - Yogi Pratama; Rahmat Kurniawan; Pujiyanto Pujiyanto (IC-ITECHS, 2022)
SLB Sumber Dharma Malang City is an educational institution for mild mentally retarded, physically handicapped, and autistic children. SDLB Sumber Dharma Malang city does not yet have teaching media with visuals regarding daily activities that are clear and appropriate for SDLB students. Through the development of the SDLB book media entitled